1994
DOI: 10.3354/meps106249
|View full text |Cite
|
Sign up to set email alerts
|

Effect of environmental contaminants on the health of Mytilus edulis from Puget Sound, Washington, USA. I. Cytochemical measures of lysosomal responses in the digestive cells using automatic image analysis

Abstract: Lysosomal responses in the digestive cells of Mytilus eduljs from 9 sites in Puget Sound, Washington. USA, with varying degrees of sediment contamination were measured using automatic image analysis. Mussels from urban-associated sltes (areas with elevated sediment concentration of anthropogenic contaminants such as PAHs, PCBs. DDTs, and toxic elements) showed pathological changes in the lysosomes (reduced lysosomal labilization period, reduced lysosomal stability and increased N-acetyl P-hexosaminidase activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
0
14

Year Published

1995
1995
2012
2012

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 132 publications
(54 citation statements)
references
References 31 publications
3
37
0
14
Order By: Relevance
“…Pronounced accumulation of lipofuscin in fish liver and mussel digestive gland has been associated with oxidative stress caused by pollution with PAHs (Krishnakumar et al, 1994(Krishnakumar et al, , 1997Au et al, 1999;Au, 2004). In our study, lipofuscin did not accumulate in phenanthrene-exposed gonads, consistent with a previous study where exposure to even 500 mg L À1 of phenanthrene for 20 days did not result in elevated amounts of lipofuscin in ovaries of P. miliaris (Schäfer and Köhler, 2009).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Pronounced accumulation of lipofuscin in fish liver and mussel digestive gland has been associated with oxidative stress caused by pollution with PAHs (Krishnakumar et al, 1994(Krishnakumar et al, , 1997Au et al, 1999;Au, 2004). In our study, lipofuscin did not accumulate in phenanthrene-exposed gonads, consistent with a previous study where exposure to even 500 mg L À1 of phenanthrene for 20 days did not result in elevated amounts of lipofuscin in ovaries of P. miliaris (Schäfer and Köhler, 2009).…”
Section: Discussionsupporting
confidence: 92%
“…Lipofuscin, also known as fluorescent age pigment, is an end product of protein and lipid peroxidation which accumulates as an ultimate consequence of oxidative stress (Au et al, 1999;Au, 2004;Terman and Brunk, 2004). In mussels and fish, contamination with PAHs has been associated with a more pronounced accumulation of lipofuscin in polluted groups compared to control groups (Krishnakumar et al, 1994(Krishnakumar et al, , 1997Au et al, 1999;Au, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, we also observed a significant increase in CAT, a marker of peroxisome proliferation, and a suppression of GGT activity in mussels from the urbanassociated sites compared to those from the reference sites. Although the observed proliferation of peroxisomes could be a secondary response to nutritional differences amongst the sites, we reported in our previous study that particulate organic matter at all the sites were sufficient for normal growth (Krishnakumar et al 1994). Furthermore, in a preliminary laboratory study, we observed increased proliferation of peroxisomes in Mytilus edulis exposed via diet to a mixture of PAHs or PCBs (Krishnakumar unpublished data), supporting our field study results.…”
Section: Discussionsupporting
confidence: 78%
“…A more detailed description of the concentrations of organic and metal contaminants in mussel tissues from these sites has been given by Krishnakumar et al (1994).…”
Section: Tissue Chemical-contaminant Burdenmentioning
confidence: 99%
“…El fl uoranteno es más persistente que los compuestos más ligeros del grupo y se acumula en mayor proporción con respecto a los mismos tal y como se ha reportado en evaluaciones realizadas con otras especies de moluscos (Hellou et al 1993, Krishnakumar et al 1994. Su rápido incremento en concentración frente al naftaleno se relaciona con los diferentes grados de afi nidad lipofílica, toxicidad y persistencia de los HAP, que son más elevados cuanto mayor es el número de anillos de la molécula; su posterior descenso sugiere un proceso de depuración tras alcanzar un determinado nivel de incorporación, tal y como se ha observado en otros invertebrados expuestos a este compuesto (Krishnakumar et al 1997;Landrum et al 2002).…”
Section: Discusionunclassified